2022
DOI: 10.2147/opth.s355899
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye Disease Symptoms and Its Association with Daily Beverage Intake Among Adults in Saudi Arabia

Abstract: Purpose To evaluate the association between dry eye disease (DED) symptoms and daily beverage intake among adults in Saudi Arabia. Patients and Methods In this cross-sectional, questionnaire-based study, we distributed an online questionnaire to men and women older than 18 years living in Saudi Arabia. The questionnaire consisted of items related to the sociodemographic characteristics of the participants and two validated indices: the Ocular Surface Disease Index (OSDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A study conducted in the Northern European population showed that sleep quality was significantly reduced in participants with dry eye disease, even after correcting for comorbidities [ 37 ]. A study from 2022 researched the association between DED symptoms and daily beverage intake, but no significant association was found [ 38 ]. In the current paper, we did not investigate these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the Northern European population showed that sleep quality was significantly reduced in participants with dry eye disease, even after correcting for comorbidities [ 37 ]. A study from 2022 researched the association between DED symptoms and daily beverage intake, but no significant association was found [ 38 ]. In the current paper, we did not investigate these aspects.…”
Section: Discussionmentioning
confidence: 99%